2021
DOI: 10.1002/slct.202102349
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Anatase/Brookite Mixed Phase TiO2 Nanostructures and its Photocatalytic Performance Study

Abstract: The TiO 2 nanostructures were prepared using hydrothermal reaction technique at different reaction temperatures viz., 120°C, 160°C, and 200°C for 24 h. The synthesized TiO 2 nanostructures was characterised by various spectroscopic techniques. XRD indicate the formation of highly crystalline nano size particles of anatase phase of TiO 2 along with minor percentage of brookite phase. Diffuse reflectance UV-Visible spectroscopy depicts the band gap around 3.2 eV. The FE-SEM shows formation of spherical particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The degradation efficiency of the hydrothermal nanoparticles increased after calcination at 400 • C (T htc ), as observed in the absorbance profile of the reaction mixture shown in Figure 10d, although its degree of crystallinity decreased upon calcination. This is because T htc is a mix of the anatase and brookite phases of TiO 2 , which is well known to have much better photocatalytic efficiency than pure anatase or brookite due to a synergistic effect that facilitates charge separation and reduces electron-hole recombination [40][41][42]. This fact is also reflected in the large red shift of the absorption maxima of the nanoparticle dispersion in UV-visible spectra of T htc in our study (cf.…”
Section: Photocatalytic Degradation Of Cationic Mb Dye Under Uv-b Irr...mentioning
confidence: 56%
“…The degradation efficiency of the hydrothermal nanoparticles increased after calcination at 400 • C (T htc ), as observed in the absorbance profile of the reaction mixture shown in Figure 10d, although its degree of crystallinity decreased upon calcination. This is because T htc is a mix of the anatase and brookite phases of TiO 2 , which is well known to have much better photocatalytic efficiency than pure anatase or brookite due to a synergistic effect that facilitates charge separation and reduces electron-hole recombination [40][41][42]. This fact is also reflected in the large red shift of the absorption maxima of the nanoparticle dispersion in UV-visible spectra of T htc in our study (cf.…”
Section: Photocatalytic Degradation Of Cationic Mb Dye Under Uv-b Irr...mentioning
confidence: 56%
“…Structure analysis Additionally, the diffraction peak at the 2θ value of 30.8° corresponded to the (121) crystal planes of brookite phase TiO 2 (JCPDS 29-1360) (Singh et al 2020). This indicated that the prepared TiO 2 was in the mixed crystal phase, which had more excellent photocatalytic performance (Jawale et al 2021). The characteristic peaks of the prepared TGs composites were found to be similar to those observed in neat TiO 2 , while no discernible characteristic peaks associated with N-GQDs were detected.…”
Section: Resultsmentioning
confidence: 93%
“…The photocatalytic hydrogen evolution via water splitting over prepared SnS 2 and Ni-SnS 2 nanostructures was performed as per the previously reported method. 23 The cylindrical quartz vessel reactor (100 ml size) was used for photocatalytic H 2 generation. The system was sealed with a septum arrangement to remove the evolved gas through a gas-tight syringe for quantifying the amount of gases evolved.…”
Section: Photocatalytic Activity Measurementmentioning
confidence: 99%
“…has been used as a potential photocatalyst. 21–45 However, the conversion efficiency of photon energy into H 2 of the studied photocatalytic materials is limited by the factors such as poor absorption ability of the visible light, fast recombination of photoexcited charge carriers, low surface catalytic reaction efficiency, poor stability, etc. Since from a few decades, researchers have proposed many different strategies or routes to overcome these restrictions, including co-catalyst loading, crystal facet engineering, construction of different surface morphology with porous structure, band gap engineering, and construction of homo or hetero-junctions (binary, ternary), etc.…”
Section: Introductionmentioning
confidence: 99%